2019
DOI: 10.1186/s13046-019-1167-2
|View full text |Cite
|
Sign up to set email alerts
|

MAPKAPK2 plays a crucial role in the progression of head and neck squamous cell carcinoma by regulating transcript stability

Abstract: Background Head and neck squamous-cell carcinoma (HNSCC) ranks sixth among cancers worldwide. Though several molecular mechanisms of tumor initiation and progression of HNSCC are known, others remain unclear. Significance of p38/MAPKAPK2 (Mitogen-activated protein kinase-activated protein kinase-2) pathway in cell stress and inflammation is well established and its role in tumor development is being widely studied. Methods We have elucidated the role of MAPKAPK2 (MK2) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 40 publications
11
34
0
Order By: Relevance
“…To solve this problem and effectively inhibit p38MAPK, researchers turned their focus to many of its downstream targets, such as MAPKAPK2. Previous studies have shown that targeting MAPKAPK2 to interdict its downstream events is as good as direct upstream inhibition of the p38MAPK pathway without obvious side effects of p38MAPK inhibitors (38)(39)(40). In the present study, we have demonstrated a direct binding between MAPKAPK2 and Sophoridine by DARTS assay and CETSA.…”
Section: Discussionsupporting
confidence: 65%
“…To solve this problem and effectively inhibit p38MAPK, researchers turned their focus to many of its downstream targets, such as MAPKAPK2. Previous studies have shown that targeting MAPKAPK2 to interdict its downstream events is as good as direct upstream inhibition of the p38MAPK pathway without obvious side effects of p38MAPK inhibitors (38)(39)(40). In the present study, we have demonstrated a direct binding between MAPKAPK2 and Sophoridine by DARTS assay and CETSA.…”
Section: Discussionsupporting
confidence: 65%
“…HNSCC is the sixth leading cancer by incidence worldwide and the eighth most common cause of cancer death [ 9 , 10 ]. Although in the past two decades new surgical and medical treatments have improved patients’ quality of life, the 5-year survival remains 40–50% of patients [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorylated MK2 and MK3 can then further activate other substrates such as cyclic AMP-responsive element binding protein (CREB) [ 40 ] and heat shock protein 27 (HSP27) to regulate actin filament remodeling [ 41 ]. MK2 is also an important regulator of post-transcriptional regulation of gene expression through modulation of adenylate-uridylate-rich elements (ARE)-binding proteins tristetraprolin (TTP) and HuR (reviewed here [ 42 ]). However, mitogen- and stress-activated kinase 1 and 2 (MSK1 and MSK2) translocate to the nucleus to mediate activation of nucleosome components and transcription factors [ 43 ].…”
Section: Classical Activation Of Mitogen-activated Protein Kinases (Mapk)mentioning
confidence: 99%
“…However, the story is complicated by a dichotomy of responses where p38 can exert both pro- and anti-inflammatory effect during disease progression. P38 can directly phosphorylate pro-inflammatory transcription factors such as MEF2C [ 168 ], and indirectly regulate inflammatory cytokine production through the MK2/3-TTP axis, where p38 phosphorylation of TTP prevents TTP-dependent degradation of AU-rich cytokine mRNA, leading to an accelerated inflammatory response [ 39 , 42 , 132 ]. As such p38 is an essential driver of inflammatory mediators such as COX2, MMP9, iNOS, TNFα, and IL6 [ 36 , 169 , 170 , 171 , 172 ].…”
Section: Pathophysiological Implications Of Mkk3/6-dependent P38 Mapksmentioning
confidence: 99%